Sustainable Language Training for Engineering Students: Integrating Resource-Efficiency into the Course Content through the Educational Process - Neil Gordon; Natalya Kemerova; Lyudmila Bolsunovskaya; Sergey Osipov (MDPI AG, 2023)
The sustainable use of the Earth's resources is recognized as increasingly important on a global scale, especially in relation to natural resource management, and is effectively addressed under the auspices of resource efficiency within engineering education. This has led to an increased demand for engineers able to carry out professional activities whilst considering sustainable issues, as well as adopting state-of-the-art technologies, and applying the best domestic and foreign practices. The study of resource efficiency encompasses a range of aspects, from natural resources, through information management, technological tools, time, and other resources. Effective engineering education should include resource efficiency, whilst enabling students to become autonomous lifelong learners, and to develop as potential researchers and professionals, able to take account of emerging issues and approaches for resource efficiency. This paper begins by analyzing the concept of resource efficiency and key research in this area. It goes on to provide a framework to demonstrate how resource-efficiency can be delivered as part of the teaching of year one engineering students, with a theoretical and methodological scaffolding. The paper presents a case study which utilizes resource efficiency within language training. The paper defines the notion of language training resources and their classification. The case study demonstrates the feasibility of the proposed approach and includes a formal assessment to show its effectiveness.